Perception of Industries on Student Performance of Bachelor of Engineering (Hons.) Electrical Engineering Program - Baharom, Rahimi; Abdul Hamid, Zulkiffli; Yusoff, Yusnani; Ihsan Mohd Yassin, Ahmad (International Journal of Engineering and Technology, 2018)
This paper presents a study on the perception of industries to the performance of Bachelor of Engineering (Hons.) Electrical Engineering students of Faculty of Electrical Engineering, Universiti Teknologi MARA (UiTM), Malaysia. This study was carried out based on the industrial training course whereby, during this period, the students are attached with the industry under supervision from their qualified personnel. After the students complete this course, they are evaluated by their industrial training supervisors using rubric measures provided by the faculty. The supervisorsâ€™ perception on the performance of all students in the degree programme (155 students) was evaluated based on the marks given to the students according to their communication skills, professionalism and work performance after completion of the industrial training. The results from the rubrics form was analysed to identify the strengths and the weaknesses of the students. The study revealed several weaknesses of students, which can be improved upon by conducting special training or courses for them to enhance their performance before graduation.Â Â